Long‐term outcome after allogeneic stem‐cell transplantation with reduced‐intensity conditioning in patients with multiple myeloma. Issue 5 (5th March 2013) - El‐Cheikh, Jean; Crocchiolo, Roberto; Furst, Sabine; Stoppa, Anne‐Marie; Ladaique, Patrick; Faucher, Catherine; Calmels, Boris; Lemarie, Claude; De, Jean‐Marc Schiano; Granata, Angela; Coso, Diane; Bouabdallah, Reda; et al.
<x xml:space="preserve">Abstract</x> This study examines the long‐term outcomes of a cohort of patients with myeloma who were treated with reduced‐intensity conditioning (RIC) regimens after a minimum follow‐up of 5 years at our centre. A total of 53 patients with multiple myeloma (MM) who received allogeneic hematopoietic stem‐cell transplantation (Allo‐SCT) between January 2000 and January 2007 were identified. The median follow‐up of living patients was 84 months (51–141). The median age of the MM patients was 50 (28–70) years. Fifty‐one patients (96%) received a transplant from a sibling donor. The median time between diagnosis and Allo‐SCT was 34 months (6–161), and the median time between auto‐SCT and Allo‐SCT was 10 months (1–89). Fifty‐one patients (96%) received at least one auto‐SCT; 24 patients (45%) received a tandem auto‐Allo‐SCT. At last follow‐up, 21 patients (40%) are alive > 5 years post RIC Allo‐SCT. At last follow‐up, 14 (26%) are in first complete remission (CR), and four patients (8%) in second CR after donor lymphocyte infusion or re‐induction with one of the new anti‐myeloma drugs (bortezomib or lenalidomide) after Allo‐SCT. Eight patients (38%) among these long survivors received one of these new drugs as induction or relapse treatment before Allo‐SCT. Disease status and occurrence of cGvHD were significantly associated with progression‐free survival (PFS); hazard ratio (HR) = 0.62 (0.30–1.29, P = 0.20). Acute GvHD was correlated with higher transplant‐related mortality; HR = 4.19 (1.05–16.77, P = 0.04). No variables were associated with overall survival (OS). In conclusion, we observe that long‐term disease control can be expected in a subset of MM patients undergoing RIC Allo‐SCT. After 10 years, the OS and PFS were 32% and 24%, respectively. The PFS curve after Allo‐SCT stabilizes in time with a plateau after 6 years post Allo‐SCT. Am. J. Hematol. 88:370–374, 2013. © 2013 Wiley Periodicals, Inc.